Resources planning for radiological incidents management - Amy Hamijah Ab. Hamid; Mohd Zaidi Abd Rozan; Roliana Ibrahim; Safaai Deris; Muhd. Noor Muhd. Yunus (American Institute of Physics, 2017)
Disastrous radiation and nuclear meltdown require an intricate scale of emergency health and social care capacity planning framework. In Malaysia, multiple agencies are responsible for implementing radiological and nuclear safety and security. This research project focused on the Radiological Trauma Triage (RTT) System. This system applies patient’s classification based on their injury and level of radiation sickness. This classification prioritizes on the diagnostic and treatment of the casualties which include resources estimation of the medical delivery system supply and demand. Also, this system consists of the leading rescue agency organization and disaster coordinator, as well as the technical support and radiological medical response teams. This research implemented and developed the resources planning simulator for radiological incidents management. The objective of the simulator is to assist the authorities in planning their resources while managing the radiological incidents within the Internal Treatment Area (ITA), Reception Area Treatment (RAT) and Hospital Care Treatment (HCT) phases. The majority (75%) of the stakeholders and experts, who had been interviewed, witnessed and accepted that the simulator would be effective to resolve various types of disaster and resources management issues.